2004
DOI: 10.1007/s00125-004-1432-5
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms of protein tyrosine phosphatase 1B gene are associated with obesity in morbidly obese French subjects

Abstract: Aims/hypothesis. The development of insulin resistance may contribute to the occurrence and progression of the metabolic syndrome associated with obesity. Components contributing to the insulin pathway and its regulation are good candidates for the molecular study of metabolic syndrome pathogenesis. Protein tyrosine phosphatase 1B (PTP 1B) is an important negative regulator of insulin. We investigated whether PTP 1B SNPs are associated with obesity and obesityrelated traits as well as global metabolic syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
29
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 38 publications
2
29
1
Order By: Relevance
“…Similarly, PTP1B re-expression in liver of PTP1B-deficient mice leads to a marked attenuation of their enhanced insulin sensitivity (14). In humans, PTP1B polymorphisms are associated with insulin resistance, obesity, or other characteristics of the metabolic syndrome in some populations (3,(15)(16)(17).Reports of PTP1B overexpression in tissues of insulin-resistant, obese, and/or diabetic animals and humans are somewhat inconsistent. Several studies have reported that PTP1B levels and activity are increased in muscle and adipose tissue of obese, insulin-resistant, and/or diabetic rodents (18 -22) and humans (23)(24)(25)(26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, PTP1B re-expression in liver of PTP1B-deficient mice leads to a marked attenuation of their enhanced insulin sensitivity (14). In humans, PTP1B polymorphisms are associated with insulin resistance, obesity, or other characteristics of the metabolic syndrome in some populations (3,(15)(16)(17).Reports of PTP1B overexpression in tissues of insulin-resistant, obese, and/or diabetic animals and humans are somewhat inconsistent. Several studies have reported that PTP1B levels and activity are increased in muscle and adipose tissue of obese, insulin-resistant, and/or diabetic rodents (18 -22) and humans (23)(24)(25)(26).…”
mentioning
confidence: 99%
“…Similarly, PTP1B re-expression in liver of PTP1B-deficient mice leads to a marked attenuation of their enhanced insulin sensitivity (14). In humans, PTP1B polymorphisms are associated with insulin resistance, obesity, or other characteristics of the metabolic syndrome in some populations (3,(15)(16)(17).…”
mentioning
confidence: 99%
“…PTP1B, which is widely expressed and localizes predominantly to the endoplasmic reticulum (5, 6), is a major IR phosphatase (7, 8), dephosphorylates IR preferentially at the tandem Tyr 1162 and Tyr 1163 residues in vitro (9) and in cultured cells (10), and may also dephosphorylate IRS-1 (11, 12). Its expression and activity are increased in obese and insulin-resistant human subjects as well as in some obese rodent models (13-16), and some studies suggest that PTP1B polymorphisms may be associated with obesity and insulin resistance in humans (17)(18)(19). The overexpression of PTP1B in muscle results in insulin resistance (20).…”
mentioning
confidence: 99%
“…In humans, PTPN1, the gene coding for PTP-1B, maps to a region in which a major human quantitative trait locus for obesity and type 2 diabetes has been reported (8 -10). Several rare PTPN1 single nucleotide polymorphisms (SNPs) have been shown to be associated with insulin resistance and diabetes in different populations (11)(12)(13)(14). Recently, Palmer et al (15) mounted an extensive study of 35 SNPs spanning a 161-kb region including the PTPN1 gene in Ͼ800 Hispanic Americans.…”
mentioning
confidence: 99%